The influence of neighbourhood units in activity patterns and linkages - Schliemann, C. W. E.(Christopher Willem Engelbert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in town and regional planning) -- University of Stellenbosch, 1987.